Representation and circulation of One Flew over the Cuckoo’s Nest in Turkish through paratexts - Sağlam, Naciye (My University, 2022)
The study seeks to provide insight to the multi-faceted translation process of One Flew over the Cuckoo’s Nest during its national and international circulation in intersemiotic and interlingual translation. Written first as a novel by Ken Kesey in 1962, the book was adapted to stage by Dale Wasserman in 1963 and into a movie in 1975 by Miloš Forman. Starring Jack Nicholson as the main character, the movie won numerous awards and the symbolic capital of the movie surpassed the book in the international circulation. In other words, the target text outpaced the original since adaptation into stage and movie can be/is perceived as a form of translation, in the form of translation of linguistic material into multimodal forms on screen or stage. The focus of the study is to examine the motives and the strategies on the interlingual translations of the novel into Turkish through paratextual elements; front and back covers as well as the prefaces. However, stage and movie adaptations will pave the way for such an analysis as the three translation practices are connected. The book One Flew over the Cuckoo’s Nest was translated into Turkish and published first in 1976 and numerous other retranslations were released in Turkish literary field up till 2018. The use the symbolic capital of Jack Nicholson who starred the main character in the movie was the primary strategy in the book covers. However, the directions of labeling may be interpreted as varying according to the strategies of publishers through back covers and prefaces.
Keywords: Tarih; Sosyal Çalışma; Eğitim; Eğitim Araştırmaları; Beşeri Bilimler; Edebiyat